PENGARUH STRATEGI PEMBELAJARAN SCIENTIFIC INQUIRY BERBANTUAN PICTORIAL RIDDLE TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII SMP NEGERI 13 PADANG - Aria Ulfa; Djusmaini Djamas; Ratnawulan Ratnawulan (Universitas Negeri Padang, 2015)
The low physics student learning achievement at SMPN 13 Padang were caused by the lack of students effort learn actively and the task that are given is not done, and almost 50% of students task showed the same result, so that students understanding about the materials was still low. Some way to increase learning achievement of students are doing scientific inquiry strategy by pictorial riddle. This research almed to observe the influence of implementation of scientific inquiry assisted learning strategy by pictorial riddle. Research type is quasi experimental with randomized control group design. This research was done at class VIII SMPN 13 Padang. Cluster sampling technique use to take two class as sample class, the choosen class were VIII4 and VIII5. Data student learning outcomes in the cognitive domain of learning obtained from the test result, the affective and psychomotor domains derived from the observation sheet. Learning outcomes analysis technique used is the average similarity of two test at the 0,05 significance level for the cognitive and psychomotor domains, whwre as affective domain through the interpretation of data shown in the graph qualitatively. Data were taken through test for cognitive aspect, through observation sheet for affective aspect and psychomotor aspect. The result showed that average test mark were 73.89 in experimental class and 64.93 in control class. In affective aspect, the average mark were 79.88 in experimental class and 71.82 in control class. Then in the psychomotor, the average mark were 77.36 in experimental class and 72.47 in control class. The conclusion this hypothesis is the implementation of scientific inquiry assisted learning strategy by pictorial riddle can increase VIII grade students outcomes in IPA subject especially in physic in SMPN 13 Padang